Gentrification, Education and Exclusionary Displacement in East London. (30th January 2013) - Butler, Tim; Hamnett, Chris; Ramsden, Mark J.
Abstract In this article we draw on Peter Marcuse's discussion of different types of displacement using evidence from a recent study we conducted in East London to argue that there is clear evidence of 'exclusionary displacement' and 'displacement pressure' in terms of education and specifically the choice of schooling. We show how the incoming middle classes in the Victoria Park area of inner East London have displaced not only existing poor residents but also many of the less affluent middle class from the favoured state schools in the area by adopting some schools and avoiding others. The preferred schools are often praised to the heavens whilst the shunned schools are similarly disparaged and deemed unacceptable. We suggest that it is this middle‐class dichotomization of schooling which accounts for the kind of educational displacement we have observed. The main form that this takes is direct exclusionary displacement when middle‐class pressure on favoured schools leads to local people being unable to get their children into them — normally because of 'distance from school' selection criteria.